Fuzzy logic controller design for inverted pendulum system - Ismail, Nurfakhirah (2013)
Inverted pendulum system is unstable without control, that is, the pendulum wills simply fall over if the cart isn’t moved to balance it and naturally falls downward because of gravity. Thus, the inverted pendulum system is inherently unstable. In order to keep it upright, or stabilize this system, one needs to manipulate it, either vertically or horizontally and it requires a continuous correction mechanism to stay upright since the system is unstable, non-linear and non-minimum phase behavior. To overcome this problem, the fuzzy logic controller will be designed. The Fuzzy Logic Controller has been chosen to stabilize the pendulum rod and keeping the cart in a desired position. Fuzzy logic has provided a simple way without going through the mathematical approach as conventional controller in order to arrive at a definite conclusion based upon nonlinear and an unstable of inverted pendulum system. Besides that, Fuzzy logic control system (FLC) was chosen as the control technique because of its ability to deal with nonlinear systems, as well as its intuitive nature. One special feature of fuzzy logic control is that it utilizes the expertise of humans to control the physical system, so that complex system can be controlled without extensive modeling of the relationship between the input and output of the system.